Challenges in Post-cataract Surgery Nocardia Endophthalmitis: Management Strategies and Clinical Outcomes. (3rd April 2022) - Kannan, Naresh Babu; Sen, Sagnik; Lalitha, Prajna; Mishra, Chitaranjan; Rameshkumar, Gunasekaran; Hariharan, Gnanam; Siva Ganesa Karthikeyan, Rajapandian; Ramasamy, Kim
ABSTRACT: Purpose: To describe the clinical and microbiological features, management strategies, outcomes, and challenges in post-cataract surgery nocardia endophthalmitis. Methods: We evaluated 28 eyes with culture-confirmed Nocardia endophthalmitis following cataract surgery. Data were collected regarding age, gender, clinical presentation, management modalities used, and final outcomes. Results: Mean age of the patients was 66.07 + -8.6 years. Four eyes (14.3%) underwent early pars plana core vitrectomy, while 18 eyes (64.3%) underwent tap/inject regimen followed by observation for 48 h, with or without a delayed vitrectomy. Thirteen eyes (46.4%) received amikacin treatment. Visual acuity (VA) improved from presentation in 9/28 (32.1%) eyes, worsened in 14/28 (50%) eyes, and showed no change in 5/28 eyes (17.9%). Conclusions: We did not find any significant association between functional outcome and time of surgery or presenting VA. Additional amikacin may be considered if there is a strong suspicion of nocardia endophthalmitis, as it may help in achieving better anatomical outcomes.